The prevalence of pulmonary embolism in patients with COVID-19 and respiratory decline: A three-setting comparison. Issue 196 (December 2020) - Brüggemann, Renée A.G.; Spaetgens, Bart; Gietema, Hester A.; Brouns, Steffie H.A.; Stassen, Patricia M.; Magdelijns, Fabienne J.; Rennenberg, Roger J.; Henry, Ronald M.A.; Mulder, Mark M.G.; van Bussel, Bas C.T.; Schnabel, Ronny M.; van der Horst, Iwan C.C.; et al.
Abstract: Background: The risk of pulmonary embolism (PE) in patients with Coronavirus Disease 2019 (COVID-19) is recognized. The prevalence of PE in patients with respiratory deterioration at the Emergency Department (ED), the regular ward, and the Intensive Care Unit (ICU) are not well-established. Objectives: We aimed to investigate how often PE was present in individuals with COVID-19 and respiratory deterioration in different settings, and whether or not disease severity as measured by CT-severity score (CTSS) was related to the occurrence of PE. Patients/methods: Between April 6th and May 3rd, we enrolled 60 consecutive adult patients with confirmed COVID-19 from the ED, regular ward and ICU who met the pre-specified criteria for respiratory deterioration. Results: A total of 24 (24/60: 40% (95% CI: 28–54%)) patients were diagnosed with PE, of whom 6 were in the ED (6/23: 26% (95% CI: 10–46%)), 8 in the regular ward (8/24: 33% (95% CI: 16–55%)), and 10 in the ICU (10/13: 77% (95% CI: 46–95%)). CTSS (per unit) was not associated with the occurrence of PE (age and sex-adjusted OR 1.06 (95%CI 0.98–1.15)). Conclusion: The number of PE diagnosis among patients with COVID-19 and respiratory deterioration was high; 26% in the ED, 33% in the regular ward and 77% in the ICU respectively. In our cohort CTSS was not associated with the occurrence of PE. Based on the high number of patients diagnosed with PE among those scanned we recommend a low threshold for performing computed tomography angiography in patients with COVID-19 and respiratory deterioration. Highlights: The high prevalence of pulmonary embolism in COVID-19 is not limited to the ICU Respiratory deterioration in COVID-19 patients should prompt a low threshold CTPA Regular thromboprophylaxis may be insufficient to prevent PE in COVID-19 patients